Inzake : informatieblad van de AbvaKabo homo/lesbische groep. - ABVAKABO (Zoetemeer : ABVAKABO, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit : onbekend
Redactie : Postbus 3010, 2700 KT Zoetermeer
Nederlands
Periodiek